2019
DOI: 10.3390/electronics8080905
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Grid-Connected Rooftop Solar Photovoltaic System

Abstract: Turkey is among the countries largely dependent on energy import. This dependency has increased interest in new and alternative energy sources. Installation of rooftop solar photovoltaic systems (RSPSs) in Turkey is increasing continuously regarding geographical and meteorological conditions. This paper presents an insight into the potential situation for Turkey and a simulation study for the RSPS designing and calculation for the faculty building at Marmara University in Istanbul. This simulation study demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…As the plant capacity increases, the COE also goes down. Alper et al [82] studied a grid-connected rooftop PV system of 84.75kWp capacity (339 monocrystalline modules with 15.37% efficiency) in Turkey. The system produced 90,289 kWh/yr energy annually at a COE of 0.0808USD/kWh and a payback period of 12.52 yrs.…”
Section: European Regionmentioning
confidence: 99%
“…As the plant capacity increases, the COE also goes down. Alper et al [82] studied a grid-connected rooftop PV system of 84.75kWp capacity (339 monocrystalline modules with 15.37% efficiency) in Turkey. The system produced 90,289 kWh/yr energy annually at a COE of 0.0808USD/kWh and a payback period of 12.52 yrs.…”
Section: European Regionmentioning
confidence: 99%
“…Akpolat, A. N. et al [34] used PVSOL software to perform a simulation study for a project at Marmara University in Istanbul, Turkey. Simulation results showed that the 84.75kWp rooftop solar power system gave positive results.…”
Section: Thanh Ba Nguyen Phuong Hoang Vanmentioning
confidence: 99%
“…Dondariya et al [35] investigated a PV system of 6.4 kW capacity installed on the roof of a building in India but the shading advantage and self-shading effect of the PV modules was not included in their research work. Akpolat et al [36] analyzed a roof integrated PV setup for Marmara University's staff building in Turkey. Their roof integrated PV system achieved a 73% performance ratio.…”
Section: Introductionmentioning
confidence: 99%